Implementasi Kurikulum Terpadu Agama dan Sains dalam Pembentukan Karakter Siswa Sekolah Menengah Pertama - Malik, Abd (Impressive: Journal of Education, 2024)
This study aims to analyze the implementation of the integrated curriculum of Religion and Science in character development of students at MTs Nurul Cholil Bangkalan. A qualitative approach with a case study design was employed. Data were collected through participatory observation, in-depth interviews with the principal, teachers, and students, as well as documentation related to the curriculum implementation. Data analysis was conducted using techniques of data reduction, data presentation, and drawing conclusions. The findings indicate that the integration of religious values and science in learning has positively impacted students' character development, such as enhanced discipline, responsibility, and empathy. However, challenges exist regarding the readiness of human resources and infrastructure that need to be addressed to maximize the effectiveness of this integrated curriculum implementation. Recommendations from this study include the necessity for continuous training for educators and improvement of supporting facilities to sustain the integration of the Religion and Science curriculum in students' character development.